The Effectiveness of Inquiry-Based Learning in Enhancing Critical Thinking Skills among Student - Eka Setiawati; Yeti Nurdiati (CV Kalimasada Group, 2025)
The purpose of this study is to examine the effectiveness of inquiry-based learning in enhancing critical thinking skills among students. Inquiry-based learning, as an instructional approach, encourages learners to actively explore problems, raise questions, and construct knowledge through investigation and reflection. This research employs a quantitative approach with a quasi-experimental design, involving a control group and an experimental group that implemented inquiry-based learning strategies. Data were collected using critical thinking skill tests and analyzed through statistical techniques to determine significant differences between groups. The findings indicate that students who engaged in inquiry-based learning demonstrated higher levels of critical thinking, particularly in areas of analysis, evaluation, and problem-solving, compared to those taught with conventional methods. These results suggest that inquiry-based learning can be an effective pedagogical strategy to foster critical thinking skills, making it highly relevant for educational practices in the 21st century.